(untitled) (Research, Society and Development, 2022)
The Covid-19 pandemic caused profound impacts and transformations in various sectors of society on a global scale. In the educational field, replacing face-to-face education activities, Emergency Remote Teaching was adopted by most institutions as a measure to contain and prevent infection by the new SARS-CoV-2 coronavirus and its variants. In the State of Amazonas, this reality was no different. Considering the challenges of this public education, and digital inclusion, the objective of this article is presented as the context of the Faculty of Education of the Federal University of Amazonas, in the context of Licentiate of the Federal University of Amazonas, as activities of the democratic discipline Social Movements and Education that were developed through the ERE, due to the pandemic scenario. This is a qualitative research in which the Google Forms form was used as a tool for collecting information, in addition to a bibliographic and documentary support. The results reveal that there are benefits of the ERE without limits and construction limits, and with regard to the disciplines Social Movements and Education in the Pedagogy course at Faced/UFAM, this was a challenging terrain and at the same time fruitful for the construction of knowledge of the students. services.